Parasitological report of Triakis maculata (Kner & Steindachner, 1867) «Spotted houndshark» (Chondrichthyes: Selachimorpha) at the Chorrillos fishing terminal, Lima, Perú - Arrese-Dávila, Vania (2021)
The aim of this study was to describe the parasitic fauna of Triakis maculata (Kner y Steindachner, 1867), a species of shark sold for human consumption, to determine the possible presence of parasites of implication in public health. In total, 14 T. maculata individuals acquired at the Chorrillos Fishing Terminal, Lima, Peru was evaluated. Seven species of parasites were found, including monogeneous (Erpocotyle sp), nematodes (Proleptus sp), cestodes (Paraorygmatobothrium sp and Callitetrarhynchus sp.) and copepods (Achtheinus sp, Caligus sp and Lernaeopoda sp). A higher prevalence of the Paraorygmatobothrium sp cestode (64.3%) was found. None of the parasites found is zoonotic.